Potential role of bacterial pathogens in the immunopathogenesis of ovarian cancer - Wierzbińska, Wiktoria; Kuźmycz, Olga (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
The development of next-generation sequencing (NGS) techniques allowed conducting research with greater efficiency and determining the microbial pattern of niches in the human body that were previously considered sterile. Observed changes in the microbiome composition of patients with cancer lesions increasingly indicate the role of microorganisms in the tumour induction and progression. Overgrowth of certain pathogenic strains within the tissue may cause inflammation, which in its chronic form may lead to destabilization of host genome. Such changes may result in altering the expression of genes encoding proteins involved in significant metabolic pathways and promote pathogenic cell functions such as proliferation stimulation, apoptosis inhibition and modulation of inflammatory response. Consequently, these events may lead to tissue destruction, disruption of physiological processes and development of disease states including cancer. In light of emerging reports on the role of changes in the composition of the microbiota in tumorigenesis induction and the presence of pathogenic strains in the ovarian cancer (OC) tumour microenvironment (TME), the hypothesis of a potential role for bacteria in the pathogenesis of this cancer is also gaining interest. The following review presents a summary of scientific research indicating potential role of TME bacteria in the immunopathogenesis of OC.